Uso de biofertilizantes provenientes da cana energia e da cana-de-açúcar como alternativa para produção de crotalaria e soja - Sousa, Jéssika Lorrine de Oliveira (2018)
The large generation of waste from the sugar and alcohol industry has long been cause for concern with its adequate final disposal. Due to the composition of these residues with high contents of organic matter and nutrients one of the most efficient forms of destination is the addition to the soil as a source of fertilization, providing several nutrients to the crops. Another alternative is the anaerobic biodigestion, carried out to produce energy through the biogas generated in the biodigestion, that process originates from another residue (biodigested biomass concentrate) that may also have potential use as an organic fertilizer. Knowing the lack of information and research on the effects of this nutrient source on crotalaria and soybean crops, this work aims to improve the use of agricultural residues from the sugarcane sector and in other crops, and to evaluate the effects on soil chemistry of the application of vinasse and biofertilizer originating from the biodigestion of energy cane in the crotalaria and soybean crop in canevial reforestation. The experiment was conducted in a greenhouse of the UFG. An Eutrophic RED-YELLOW LATOSOL and a randomized block design were used, four doses of the biofertilizer (0, 0.5, 1, 2 and 3 times the recommended dose of 100 m3 ha-1) and a treatment with pure vinasse and the control, totaling 6 treatments with five replicates. The biofertilizer consisted of a blend of cane energy biodigested + vinasse in natura in different concentrations. The species used were Crotalaria juncea, as green manure, and Soy as a profitable crop, planted in 5 kg pots of soil. The applications were done every two days until the dose was completed. Crotalaria was cut at flowering, the leaves were separated for foliar nutritional analysis, the plant was weighed to determine green mass and dry mass of the aerial part and then it was placed in the vessel to supply organic matter. Samples of the initial soil and each treatment after each crop were cut, to determine macro and micronutrients. For the crotalaria, there was a positive response to the application of the biofertilizer in its development, with increase of the biomass production according to the increase of the dose, also presenting a higher leaf content of nutrients such as N, K and Zn, no symptoms of toxicity were observed with nutrients above adequate levels due to the rusticity of the species. For the soybean, there was also a significant response, reaching the optimum dose of 220 m³ ha-1, for larger values there was a drop in production. For both crops, the results of fresh vinasse resembled the lower doses of the biofertilizer and the control, without large increases of nutrients in the soil and leaf. For the soil variables, in general the biofertilizer presented efficiency in the availability of a large part of macro and micronutrients. Reduced acid values and pH increases and H + Al reduction occurred for soil in crops, in addition to a significant increase in base saturation and potassium (K), the most abundant nutrient in the residue used in the study.